Hygiene Status of Over-the-Row Blueberry Machine Harvesters Cleaned and Sanitized Using Various Approaches - Yaxi Dai; Renee Holland; Sarah Doane; Weiqiang Yang; Jinru Chen (Horticulturae)
Contamination of fresh blueberries via contact with an equipment surface is an important food hygiene/safety issue. In this study, four and six over-the-row blueberry machine harvesters in Georgia or Oregon were each sampled twice on two different harvest days in the 2022 harvest season. Nine sites on the top loaders (n = 8) and seven sites on the bottom loaders (n = 2) were sampled before and after cleaning/sanitation. Populations of total aerobes (TA), total yeasts and molds (YM), total coliforms (TC), and the presence of fecal coliforms (FC) and enterococci (EC) in collected samples were determined. Data collected was analyzed using the split-plot ANOVA of SAS. On average, cleaned/sanitized surfaces had about one log lower (p ≤ 0.05) TA and YM counts than the uncleaned surfaces, while no difference in TC counts was observed. The vertical and horizontal conveyors and fruit-catch plates had significantly higher TA, YM, and TC counts than other sampled sites. FC and EC were detected in 7.8% or 14.1% of the Georgia samples and 5.6% or 10.2% of the Oregon samples. The type and concentration of sanitizers and frequency and approach of cleaning/sanitation treatments all impacted the hygiene status of berry-contact surfaces of machine harvesters.